Basophil activation test: Mechanisms and considerations for use in clinical trials and clinical practice. Issue 8 (27th February 2021) - Santos, Alexandra F.; Alpan, Oral; Hoffmann, Hans‐Jürgen
Abstract: The basophil activation test (BAT) is a functional assay that measures the degree of degranulation following stimulation with allergen or controls by flow cytometry. It correlates directly with histamine release. From the dose‐response curve resulting from BAT in allergic patients, basophil reactivity (%CD63 + basophils) and basophil sensitivity (EC50 or similar) are the main outcomes of the test. BAT takes into account all characteristics of IgE and allergen and thus can be more specific than sensitization tests in the diagnosis of allergic disease. BAT reduces the need for in vivo procedures, such as intradermal tests and allergen challenges, which can cause allergic reactions of unpredictable severity. As it closely reflects the patients' phenotype in most cases, it may be used to support the diagnosis of food, venom and drug allergies and chronic urticaria, to monitor the natural resolution of food allergies and to predict and monitor clinical the response to immunomodulatory treatments, such as allergen‐specific immunotherapy and biologicals. Clinical application of BAT requires analytical validation, clinical validation, standardization of procedures and quality assurance to ensure reproducibility and reliability of results. Currently, efforts are ongoing to establish a platform that could be used by laboratories in Europe and in the USA for quality assurance and certification.